Emigracyjne życie Elżbiety Bośniackiej w świetle jej korespondencji - Iwona Gosik-Kapelińska (Annales Universitatis Paedagogicae Cracoviensis. Studia Poetica, 2017)
Emigration life of Elżbieta Bośniacka in light of her correspondence The subject of the considerations contained in this article is the part of the epistolary legacy still existing in the form of the manuscripts from the collection of Teofil Lenartowicz. They were written by Elżbieta Bośniacka, a well-known poet and playwright writing in the nineteenth century, whose most popular play Defense of Częstochowa enjoyed a permanent presence on the stage of theaters in Poland and abroad. Correspondence between the two writers is also an excellent testimony to the reconstruction of the unknown enough history of the Adam Mickiewicz Academy of Literature in Bologna, which was an important institution for scientific reasons, the popularization of knowledge, as well as political field.